Perancangan Program Aplikasi Market Basket Analysis untuk Mendukung Persediaan Barang dengan Metode Fuzzy C-Covering - Zahedi Zahedi; Charies Chandra (Bina Nusantara University, 2012)
Any difficulty in analyzing sales transaction data is often faced by a company due to the huge number of sales transactions and the limited tools to process the data. It results in losses for the company since it is difficult to estimate the goods supply for subsequent sales. In this paper a data mining application is designed to analyze sales data. Market Basket Analysis is a data mining application that aims to determine most purchased or used products at once by the consumer. The process of Market Basket Analysis is to analyze consumer buying habits by finding associations among products purchased by different customers. The method used in Market Basket Analysis is a method of Fuzzy c-Covering, which is one method to classify the elements of a universal set into partitions of fuzzy sets. This study found that the value of support and confidence is part of the Market Basket Analysis, computed using the Fuzzy c-Covering. The higher the limit, the more selected the analytical results obtained are.